Teachers’ expectations of performance in teaching and their achievement experiences: the Tanzanian context - Bihu, Reuben; Boniface, Raymond Mwemezi (Papers in Education and Development, 2024)
At the start of their careers, teachers often hold high expectations for their professional achievements, yet the realities they encounter may not always align with these initial aspirations. This study, grounded in a constructivist paradigm, investigated secondary school teachers’ career entry expectations and their subsequent achievement experiences. A case study approach was employed, utilising semi-structured interviews with secondary school teachers and unstructured interviews with educational leaders to gain insights into how teachers’ expectations are perceived and discussed in their settings. The findings reveal that good performance in teaching is a key professional expectation for teachers entering the field. While teachers initially hold high expectations for their work performance, their actual experiences range from high achievement to average, low, and even failure. The study recommends fostering corporate social responsibility in schools as a means to enhance teachers’ performance experiences and support their professional growth.